PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPETENSI DAN SERTIFIKASI KEAHLIAN TERHADAP KINERJA PEGAWAI PADA BPKP PERWAKILAN PROVINSI JAWA TIMUR - Soffin Ubaidillah; Purwanto Purwanto; Anita Kartika Sari (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the effects of transformational leadership, competence, and professional certification on employee performance at the East Java Representative Office of the Financial and Development Supervisory Agency. A quantitative approach with a causal associative design was employed. The population consisted of 208 employees, all of whom were selected as respondents through a census method. Data were collected using questionnaires and analyzed through multiple linear regression with SPSS. The results indicate that transformational leadership has a positive and significant effect on employee performance with a beta coefficient of 0.582. Competence also has a positive and significant effect with a beta coefficient of 0.230, while professional certification has a positive and significant effect with a beta coefficient of 0.356. Simultaneously, the three independent variables significantly affect employee performance, as indicated by an F-value of 235.385 and a significance level of 0.000. The Adjusted R Square value of 0.773 shows that 77.3% of the variation in employee performance can be explained by the three variables. Transformational leadership is identified as the most dominant predictor. These findings highlight the importance of strengthening leadership practices, developing employee competence, and providing relevant professional certification.